Proceedings of the 2nd Borobudur International Symposium on Humanities and Social Sciences, BIS-HSS 2020, 18 November 2020, Mag 2021
DOI: 10.4108/eai.18-11-2020.2311667
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Panic Buying Behavior from Fear of Covid-19 and Citizen Trust

Abstract: Early in 2020 China, Japan, and dozens of other countries were busy with a terrible and deadly disease outbreak, Novel Coronavirus Diseases (COVID-19). Then, the spread of this virus is very concerned about it because of its very rapid spread through air media or fluids from the respiratory tract. This phenomenon has a significant impact on life globally. Anxiety, panic, and public fear of the virus create a new lifestyle that must be controlled by oneself. The health, economic, educational, political, social,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Furthermore, the findings of this study indicated that there is a positive relationship between the fear of COVID-19 and panic buying behavior. This finding supports other study by Akhrani et al, (2020) that argued the fear of COVID-19 influences panic buying behavior. The researchers suggest that the positive relationship between the fear of COVID-19 and panic buying behavior is instigated by the customer's fear of complete lock down that could be implemented by the government to decrease the cases and the prevalence of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, the findings of this study indicated that there is a positive relationship between the fear of COVID-19 and panic buying behavior. This finding supports other study by Akhrani et al, (2020) that argued the fear of COVID-19 influences panic buying behavior. The researchers suggest that the positive relationship between the fear of COVID-19 and panic buying behavior is instigated by the customer's fear of complete lock down that could be implemented by the government to decrease the cases and the prevalence of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…The considerable direct and indirect correlations among the investigated variables confirm previous researchers' argument that fear of COVID-19, severity perceptions, scarcity perceptions, and anxiety are critical precursors to panic buying. (Kemp et al, 2014;Liren et al, 2012;Sim et al, 2020;Yuen et al, 2020;Akhrani et al, 2020;Omar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations